2021
DOI: 10.1111/nph.17382
|View full text |Cite
|
Sign up to set email alerts
|

A hundred years after: endodormancy and the chilling requirement in subtropical trees

Abstract: Endodormancy and the related chilling requirement synchronize the seasonal development of trees from the boreal and temperate regions under the climatic conditions prevailing at their native growing sites. The phenomenon of endodormancy has been known at the whole-plant level for 100 years, and in the last couple of decades, insights into the physiological and molecular basis of endodormancy and its release have also been obtained. Intriguingly, recent studies have shown experimentally that subtropical trees a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…This is in line with recent studies, which show that several subtropical tree species have a rest period and a chilling requirement ( Du et al, 2019 ; Song et al, 2020 ; Pan et al, 2021 ; Zhang et al, 2021a , b ). The novelty and scarcity of these findings in the case of subtropical trees are in striking contrast with the case of boreal and temperate trees, where the existence of these traits has already been known for a 100 years ( Coville, 1920 ; Jewaria et al, 2021 ).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…This is in line with recent studies, which show that several subtropical tree species have a rest period and a chilling requirement ( Du et al, 2019 ; Song et al, 2020 ; Pan et al, 2021 ; Zhang et al, 2021a , b ). The novelty and scarcity of these findings in the case of subtropical trees are in striking contrast with the case of boreal and temperate trees, where the existence of these traits has already been known for a 100 years ( Coville, 1920 ; Jewaria et al, 2021 ).…”
Section: Discussionmentioning
confidence: 87%
“…However, the value is well in line with the experimental results available for subtropical trees. Zhang et al (2021a,c) found that in two subtropical tree species the restbreaking effect of +15 • C was equal to that of +10 and +5 • C, suggesting that in subtropical trees T upp can even be well above +15 • C (refer to also Jewaria et al, 2021). Further experimental studies with several controlled chilling temperatures and chilling durations (Baumgarten et al, 2021;Zhang et al, 2021a,c) are needed to test and improve the sub-model I developed for pecan seedlings in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Global warming has resulted in countless perennial plants facing incomplete endodormancy associated with insufficient CR and poses obstacles to bud sprouting (Prudencio et al, 2020;Wang et al, 2021). This hinders the ability of these plants to grow well and consequently reduces their economic value after warm winters, especially in northern cultivars grown at lower latitudes (Zhang et al, 2017;Jewaria et al, 2021). Therefore, elucidating the mechanism controlling endodormancy release may help researchers address the problems caused by warming winter climates.…”
Section: Introductionmentioning
confidence: 99%